The Rat Nervous System. - Paxinos, George (Elsevier, 2004)
This third edition of the standard reference on the nervous system of the rat is a complete and updated revision of the 1994 second edition. All chapters have been extensively updated, and new chapters added covering early segmentation, growth factors, and glia. The book is now aligned with the data available in the Rat Brain in Stereotaxic Coordinates, making it an excellent companion to this bestselling atlas. Physiological data, functional concepts, and correlates to human anatomy and function round out the new edition.